How Does Epstein–Barr Virus Interact With Other Microbiomes in EBV-Driven Cancers? - Wen, Yuxi; Xu, Huan; Han, Juan; Jin, Runming; Chen, Hongbo (Frontiers in Cellular and Infection Microbiology, 2022)
The commensal microbiome refers to a large spectrum of microorganisms which mainly consists of viruses and bacteria, as well as some other components such as protozoa and fungi. Epstein–Barr virus (EBV) is considered as a common component of the human commensal microbiome due to its spread worldwide in about 95% of the adult population. As the first oncogenic virus recognized in human, numerous studies have reported the involvement of other components of the commensal microbiome in the increasing incidence of EBV-driven cancers. Additionally, recent advances have also defined the involvement of host–microbiota interactions in the regulation of the host immune system in EBV-driven cancers as well as other circumstances. The regulation of the host immune system by the commensal microbiome coinfects with EBV could be the implications for how we understand the persistence and reactivation of EBV, as well as the progression of EBV-associated cancers, since majority of the EBV persist as asymptomatic carrier. In this review, we attempt to summarize the possible mechanisms for EBV latency, reactivation, and EBV-driven tumorigenesis, as well as casting light on the role of other components of the microbiome in EBV infection and reactivation. Besides, whether novel microbiome targeting strategies could be applied for curing of EBV-driven cancer is discussed as well.